Efficacy of foliar spray of Trichoderma isolates against Fusarium graminearum causing head blight of wheat - Panwar, Vipin; Aggarwal, Ashok; Singh, Gyanendra; Verma, Ajay; Sharma, Indu; Singh Saharan, Mahender (Journal of Cereal Research, 2014)
The bioefficacy of biocontrol agents, Trichoderma harzianum isolates (Th-M & Th-P) and Trichoderma viride isolate (Tv) was studied against Fusarium head blight pathogen of wheat (Fusarium graminearum) in vitro and under green house conditions (pot trial). Dual culture technique was used for testing the potential of Trichoderma isolates against seven isolates of F. graminearum in vitro. Trichoderma harzianum (Th-M) was found most effective in significantly reducing the radial growth of all F. graminearum isolates followed by T. viride. Foliar application of T. harzianum (M) and T. viride alone and in combination significantly reduced the disease severity as compared to control. Maximum reduction in disease severity was achieved with combined application of T. harzianum and T. viride.